2021
DOI: 10.1177/02841851211046502
|View full text |Cite
|
Sign up to set email alerts
|

COVID-19 myocarditis cardiac magnetic resonance findings in symptomatic patients

Abstract: Background Coronavirus disease 2019 (COVID-19) may cause myocardial damage. Purpose To evaluate the short-term and medium-term results, as well as the imaging features of COVID-19 cardiac involvement, using cardiac magnetic resonance (CMR). Material and Methods In this study, laboratory and CMR findings of 15 patients with COVID-19 between May 2020 and May 2021 were evaluated retrospectively. Late gadolinium enhancement (LGE) imaging was evaluated for myocarditis. Cardiac functions were quantitatively evaluate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
23
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(23 citation statements)
references
References 20 publications
(44 reference statements)
0
23
0
Order By: Relevance
“…Four of the studies presented two cohorts [ 8 , 10 , 21 , 31 ]; therefore, we included a total of 33 independent cohorts. Among the 29 included studies, nine were from the USA [ 8 , 15 , 20 , 22 , 24 , 32 , 36 38 ], six were from China [ 10 , 11 , 16 , 18 , 21 , 30 ], three each from the UK [ 19 , 22 , 26 ] and Germany [ 7 , 23 , 28 , 35 ], two each from Italy [ 9 , 27 ] and Turkey [ 29 , 31 ], and one each from Poland [ 17 ], Norway [ 34 ], Hungary [ 33 ] and Spain [ 25 ]. The publication year was 2020 or 2021 ( Table 1 ).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Four of the studies presented two cohorts [ 8 , 10 , 21 , 31 ]; therefore, we included a total of 33 independent cohorts. Among the 29 included studies, nine were from the USA [ 8 , 15 , 20 , 22 , 24 , 32 , 36 38 ], six were from China [ 10 , 11 , 16 , 18 , 21 , 30 ], three each from the UK [ 19 , 22 , 26 ] and Germany [ 7 , 23 , 28 , 35 ], two each from Italy [ 9 , 27 ] and Turkey [ 29 , 31 ], and one each from Poland [ 17 ], Norway [ 34 ], Hungary [ 33 ] and Spain [ 25 ]. The publication year was 2020 or 2021 ( Table 1 ).…”
Section: Resultsmentioning
confidence: 99%
“…Finally, 10.462 patients with COVID-19, including 1010 non-athletes and 9.452 athletes, and 746 controls were included in our analysis. A 1.5 T MR scanner was used in 15 studies [ 8 , 9 , 11 , 15 , 17 , 22 26 , 28 , 29 , 33 35 ] and a 3.0 T MR scanner was used in six studies [ 7 , 10 , 16 , 18 , 21 , 30 ], Both 1.5 T and 3.0 T scanners were used in one study [ 20 ] and data regarding MR scanners were not provided in seven studies [ 19 , 27 , 31 , 32 , 36 38 ]. As the myocardial native T1 time substantially differs between different magnetic field strengths and sequences [ 39 ], we investigated the number patients with abnormal T1 time, rather than those with absolute value of native T1 time, among the nine studies presenting the prevalence of patients with abnormal native T1 times [ 7 9 , 11 , 17 , 22 , 26 , 27 , 32 ].…”
Section: Resultsmentioning
confidence: 99%
“…We identified 648 records, from which 60 were retrieved for further analysis. Following the eligibility assessment, nineteen studies were finally included in this review [4,[24][25][26][27][28][29][30][31][32][33][34][35][36][37][38][39][40][41]; their characteristics are shown in Table 1 (Ref. [4,[24][25][26][27][28][29][30][31][32][33][34][35][36][37][38][39][40][41]).…”
Section: Cmr Findings In Recovered Covid-19 Patientsmentioning
confidence: 99%
“…Cohort description T2 (ms) 1 Visible edema (N (%)) 1 Pericardial effusion (N (%)) 1 Pericardial enhancement (N (%)) 1 Field strength = 1.5 T Kotecha et al [28] LGE data from the selected reports are summarized in Table 4 (Ref [4,[24][25][26][27][28]30,31,33,[35][36][37][38][39][40][41]). Kotecha et al [28] found significant positive LGE in 49% of the patients who recovered from COVID-19, Thornton et al [37] reported it in 56%, and Puntmann et al [35] found 32% (myocardial) and 22% (pericardial).…”
Section: Authormentioning
confidence: 99%
See 1 more Smart Citation